Investigation of the tribological performance of ionic liquids in non-conformal EHL contacts under electric field activation - Michal Michalec; Petr Svoboda; Ivan Krupka; Martin Hartl; Aleksandar Vencl (Friction)
Abstract Real-time external alteration of the internal properties of lubricants is highly desirable in all mechanical systems. However, fabricating a suitable and effective smart lubricant is a long-lasting experimental process. In this study, the film thickness and frictional response of ionic liquid-lubricated non-conformal contacts to an electric field excitation under elastohydrodynamic conditions were examined. Film thickness was evaluated using a “ball-on-disc” optical tribometer with an electric circuit. Friction tests were carried on a mini traction machine (MTM) tribometer with a “ball-on-disc” rotation module and an electric circuit for contact area excitation. The results demonstrate that there is a difference in the behaviour of the ionic liquid during electric field excitation at the evaluated film thicknesses. The results of evaluated film thicknesses demonstrate that there is a difference in the behaviour of the ionic liquid during electric field excitation. Therefore, the ionic liquids could be a new basis for the smart lubrication of mechanical components. Moreover, the proposed experimental approach can be used to identify electrosensitive fluids.